Sequential screening for depression in humanitarian emergencies: a validation study of the Patient Health Questionnaire among Syrian refugees - Poole, Danielle N.; Liao, Shirley; Larson, Elysia; Hedt-Gauthier, Bethany; Raymond, Nathaniel A.; Bärnighausen, Till; Smith Fawzi, Mary C. (Annals of general psychiatry, 2020)
Background: Despite the need for mental health surveillance in humanitarian emergencies, there is a lack of validated instruments. This study evaluated a sequential screening process for major depressive disorder (MDD) using the two- and eight-item Patient Health Questionnaires (PHQ-2 and PHQ-8, respectively). Methods: This study analyzed data collected during a cross-sectional survey in a Syrian refugee camp in Greece (n = 135). The response rate for each instrument was assessed, and response burden was calculated as the number of items completed. The sequential screening process was simulated to replicate the MDD classifications captured if the PHQ-2 was used to narrow the population receiving the full PHQ-8 assessment. All respondents were screened using the PHQ-2. Only respondents scoring ≥ 2 are considered at risk for symptoms of MDD and complete the remaining six items. The positive and negative percent agreement of this sequential screening process were evaluated. Results: The PHQ-2, PHQ-2/8 sequential screening process, and PHQ-8 were completed by 91%, 87%, and 84% of respondents, respectively. The sequential screening process had a positive percent agreement of 89% and a negative percent agreement of 100%, and eliminated the need to complete the full PHQ-8 scale for 34 (25%) respondents. Conclusions: The benefits of the sequential screening approach for the classification of MDD presented here are twofold: preserving classification accuracy relative to the PHQ-2 alone while reducing the response burden of the PHQ-8. This sequential screening approach is a pragmatic strategy for streamlining MDD surveillance in humanitarian emergencies.